The Influence of Whistleblowing System and Internal Control on Fraud Prevention at PT Pos Indonesia (Persero) Bandung City - Adi Kuncara, Wulansari (Goodwood Publishing, 2022)
Purpose: This study aims to determine how the influence of the whistleblowing system and internal controls on fraud prevention at Pos Indonesia (Persero) Bandung City. Research Methodology: The research method used in this research is descriptive and verification methods. The sampling technique used in this study is a non-probability sampling technique with a saturated sampling technique so that the total sample size is 30 people. The analytical method used in this research is multiple linear regression analysis using SPSS 25. Results: The results showed that the whistleblowing system and internal controls had an effect on fraud prevention. The amount of influence of internal control in contributing to fraud prevention is 66.2%. Limitations: This research is limited only to PT Pos Indonesia (Persero) because it still shows cases of fraud. In addition, this study only focuses on knowing the effect of the whistleblowing system and internal controls on fraud prevention at PT Pos Indonesia (Persero) Bandung City. Contributions: This research is expected to provide benefits for companies that lead to improvements in preventing fraud, and can be used as additional information for the parties concerned.